2003
DOI: 10.1063/1.1581386
|View full text |Cite
|
Sign up to set email alerts
|

Growth and optical properties of GaN/AlN quantum wells

Abstract: We demonstrate the growth of GaN/AlN quantum well structures by plasma-assisted molecular-beam epitaxy by taking advantage of the surfactant effect of Ga. The GaN/AlN quantum wells show photoluminescence emission with photon energies in the range between 4.2 and 2.3 eV for well widths between 0.7 and 2.6 nm, respectively. An internal electric field strength of $9.2\pm 1.0$ MV/cm is deduced from the dependence of the emission energy on the well width.Comment: Submitted to AP

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 24 publications
5
45
0
Order By: Relevance
“…4 The latter adverse effect has lead to the conclusion that for optimal optical devices ͑such as QW lasers͒, the maximum well thickness should be around 3 nm ͑12 DL GaN͒. 13,14 Note that in Ref. 14, the large linewidth broadening indicated severe thickness fluctuations and interface roughness, which may contribute to a prevalence of nonradiative recombination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The latter adverse effect has lead to the conclusion that for optimal optical devices ͑such as QW lasers͒, the maximum well thickness should be around 3 nm ͑12 DL GaN͒. 13,14 Note that in Ref. 14, the large linewidth broadening indicated severe thickness fluctuations and interface roughness, which may contribute to a prevalence of nonradiative recombination.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with using ͑Ga,Al͒N, using pure AlN as the barrier material leads to a stronger macroscopic polarization ͑both spontaneous and piezoelectric͒ and larger built-in electric fields. 2,13 This offers a wider range of effective band-gap ͑optical emission͒ tunability of both interband transitions 14 and improved intersubband transitions. [15][16][17] In particular, earlier experimental results for using ͑Ga,Al͒N as a barrier have shown that the band gap is set primarily by the thickness of the well layer, 16 as well as by the barrier width.…”
Section: Introductionmentioning
confidence: 99%
“…The AlN/GaN heterostructures are also of paramount importance for applications such as high electron mobility transistors (HEMTs), ultraviolet (UV) emitters and sensors, as well as optoelectronic devices based on the intersubband principle (e.g. [5][6][7][8][9][10][11][12][13]). …”
Section: Introductionmentioning
confidence: 99%
“…SLs with the same amount of dopants either in the barrier-or well-are grown and no significant structural differences were observed by XRD or AFM. In order to study the effect of doping on ISB absorption and assess the SL quality grown by our technique, we have grown 50 periods of {1.9 nm GaN with 3.1 nm AlN} SL on 600 nm AlN/c-sapphire with well doping levels of non-intentionally-doped ~10 16 , slightly-doped …”
Section: Effects Of Doping On Optical and Structural Qualitymentioning
confidence: 99%